2007
DOI: 10.1029/2006wr005184
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of hydrological models in the spectral domain: An opportunity for scarcely gauged basins?

Abstract: [1] This study considers the use of the maximum likelihood estimator proposed by Whittle for calibrating the parameters of hydrological models. Whittle's likelihood provides asymptotically consistent estimates for Gaussian and non-Gaussian data, even in the presence of long-range dependence. This method may represent a valuable opportunity in the context of ungauged or scarcely gauged catchments. In fact, the only information required for model parameterization is essentially the spectral density function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 35 publications
1
103
0
Order By: Relevance
“…To tackle this issue, recent studies (De Thomasis and Grimaldi, 2001;Chiang et al, 2002;Grimaldi, 2004;Corduas, 2011) proposed to analyze the streamflow temporal dynamics through the parameter sets of linear models estimated on the corresponding streamflow time series. A more parsimonious, but less refined and necessarily approximated, approach is applied here for representing the autocorrelation structure: in addition to the lag-1 autocorrelation coefficient (previously used in regionalisation studies, for example, by Montanari and Toth (2007);Castiglioni et al (2010); Lombardi et al (2012) for the parameterisation of a rainfall-runoff model), it is here proposed to use an index representing the shape of the ACF, i.e. the correlation scaling exponent.…”
Section: E Toth: Catchment Classificationmentioning
confidence: 99%
“…To tackle this issue, recent studies (De Thomasis and Grimaldi, 2001;Chiang et al, 2002;Grimaldi, 2004;Corduas, 2011) proposed to analyze the streamflow temporal dynamics through the parameter sets of linear models estimated on the corresponding streamflow time series. A more parsimonious, but less refined and necessarily approximated, approach is applied here for representing the autocorrelation structure: in addition to the lag-1 autocorrelation coefficient (previously used in regionalisation studies, for example, by Montanari and Toth (2007);Castiglioni et al (2010); Lombardi et al (2012) for the parameterisation of a rainfall-runoff model), it is here proposed to use an index representing the shape of the ACF, i.e. the correlation scaling exponent.…”
Section: E Toth: Catchment Classificationmentioning
confidence: 99%
“…Calibration approaches that do not rely on direct time-series versus time-series comparison are useful in such situations. Prior approaches to model calibration without direct time series comparison include calibration to spectral properties (Montanari and Toth, 2007), recession curves (Winsemius et al, 2009), slope of the flow-duration curve (Yadav et al, 2007;Yilmaz et al, 2008), base-flow index (Bulygina et al, 2009) and the use of a performance measure based on specified exceedance percentages of a synthetic regional flow-duration curve (FDC) for calibration at un-gauged sites (Yu and Yang, 2000). However, in these studies uncertainties in observed discharge are not considered explicitly.…”
Section: Introductionmentioning
confidence: 99%
“…Whittle's likelihood (Whittle, 1953) (15) is a frequency-based approximation of the Gaussian likelihood and can be interpreted as minimum distance estimate of the distance between the parametric spectral density and the (nonparametric) periodogram. It also minimizes the asymptotic KullbackeLeibler divergence and, for autoregressive processes, provides asymptotically consistent estimates for Gaussian and non-Gaussian data, even in the presence of longrange dependence (Montanari and Toth, 2007). Likelihood function 16, also referred to as Laplace or double exponential distribution, differs from all other likelihood functions in that it assumes a [ 1 -norm of the error residuals.…”
Section: Input Argument 2: Dreamparmentioning
confidence: 99%